PEMANFAATAN INTERNET SEBAGAI PENUNJANG PEMBELAJARAN SOSIOLOGI PADA SISWA KELAS XII DI SMA N 2 LUBUK BASUNG KABUPATEN AGAM - Susanti, Dia Nely; Adiyalmon, Adiyalmon; Prahara, Surya (Pendidikan Sosiologi, 2013)
Improved the knowledge and technology is more increase in the purpose of the learning process. For example, the students and teachers challenge to more creative in prepare what the material from the learning process. In new case, that come in technology and communicate study is come in net work that familiar term internet. The aim of this research is to know how to use the internet toward sociology learning process at senior high school 2 Lubuk Basung City.The researched studies do use qualitative near and descriptive type. To choose inorman this researched studies with purpose sampling that have 20 people, class XII are 17 people and the sociologyâs teachers are 3 people. Research data is data primer and data secondary. Data primer is all data that get from informan research, and data secondary is all data that get from the school as a support like documentation, data teacher and students, medium and preparation, reading book and lesson plan. After that, this is use a technique observation, interview, and documentation. All data that get to do process analysis with Trianggulasi that 5 step are, aggregation data, reduction, presentation, and come out the conclusion process.From this research, we know that the aim from the internet as guide in sociology learning process is give an easy when search sources sociology learning, tasks, extent knowledge, as a consolation, etc. But, to the teacher, internet as supporting sociology learning, make an easy to extent, material of learning, to search example lesson plan and come in new information. AlthoughÂ Â  not all students can use because studentsâ limit to get and to do.